Epidemiology of Asbestosis between 2010-2014 and 2015-2019 Periods in Colombia: Descriptive Study - Gabriel Camero; Guillermo Villamizar; Luis M. Pombo; Manuel Saba; Arthur L. Frank; Aníbal A. Teherán; Gerhard M. Acero (Ubiquity Press, 2023)
Background: Asbestosis is a prevalent worldwide problem, but scarce data sourced from developing countries are available. We describe the sociodemographic characteristics and patterns in the occurrence of care provided for asbestosis in Colombia during the periods 2010-2014 and 2015-2019 to establish the behavior, trends, and variables associated with concentrations among people attended by asbestosis. Methods: A retrospective descriptive study was carried out with data from the Integrated Social Protection Information System (SISPRO) for two 5-year periods. People attended by asbestosis (ICD-10: J61) were identified; the frequency of patient visits, sociodemographic characteristics, case distribution patterns, and trends in both five-year periods were described, as was the crude frequency (cFr, 95% CI) of asbestosis (1,000,000 people/year) in both five-year periods (cFr ratio, 95% CI). Results: During the period 2010-2019, 765 people attended by asbestosis were identified; there were 308 people attended by asbestosis between 2010-2014 (cFr: 2.20, 1.96-2.47), and ther were 457 people attended by asbestos between 2015-2019 (cFr: 3.14, 2.92-3.50). In both periods, the estimated cFr in men was nine times the estimated cFr in women. The cFr increased in the 2015-2019 period (cFr_ratio: 1.23, 1.06-1.43). Compared with the 2010-2014 period, the cFr of asbestosis increased in women (cFr_ratio: 1.44, 1.03-2.01), in the Andean (cFr_ratio: 1.61, 1.35-1.95) and Caribbean regions (cFr_ratio: 1. 66, 1.21-2.30), in the urban area (cFr_ratio: 1.24, 1.05-1.48), and in the age groups 45-59 years (cFr_ratio: 1.34, 1.001-1.79) and ≥60 years (cFr_ratio: 1.43, 1.13-1.83). Discussion: During two five-year periods, the cFr of asbestosis was higher in men; between the first and second five-year periods, it increased significantly, especially in urbanized geographic areas and in populations aged ≥45 years. The estimates possibly reflect the effect of disease latency or the expected impact of public health policies to monitor asbestos exposure and complications.